Analyzing the relationship between economic policy uncertainty and tax avoidance - Amjad Rahmanzadeh; Aram Sepehrivand (New Applied Studies in Management, Economics & Accounting, 2021)
The countries of the world differ in terms of tax structure in terms of monetary and tax systems, and this difference in the tax system is due to different social preferences for public goods over private goods. In order to balance and administer justice and prevent tax escalation in various areas, the government has set various rates for taxation, including income tax, value added tax, and consumption and sales tax. As economic policy uncertainty increases, tax avoidance strategies can be ineffective because they may not be compatible with new policies and increase the likelihood of tax evasion. This study seeks to answer the question that what is the relationship between economic policy uncertainty and tax avoidance of companies listed on the Tehran Stock Exchange. The statistical population of this study is all the companies listed on the Tehran Stock Exchange during the period 2011 to 2018. The econometric model used in this research is the panel data regression method. The results show that the effect of the independent variable of economic policy uncertainty on the tax avoidance variable of Tehran Stock Exchange companies is positive and significant. The results also show that the tax quota variable has a positive and significant adjustment effect on the relationship between economic policy uncertainty and tax avoidance of Tehran Stock Exchange companies.